2020
DOI: 10.3389/fphys.2020.00969
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Premature Ventricular Contractions From the Outflow Tract Display an Underlying Substrate That Can Be Unmasked by a Type 2 Brugada Electrocardiographic Pattern at High Right Precordial Leads

Abstract: Background: Patients with premature ventricular contractions (PVCs) from the right ventricular outflow tract (RVOT) and apparently normal hearts, can have ST elevation similar to type 2 or type 3 Brugada pattern in the electrocardiographic (ECG) performed at a higher position. Cardiac magnetic resonance (CMR), has shown conflicting data regarding existence of structural abnormalities in patients with idiopathic PVCs from the RVOT. Objective: Our aim was to evaluate the prevalence of low voltage areas (LVAs) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
4
4
0
Order By: Relevance
“…The much higher incidence of ST-segment elevation in our patients with RVOT VAs has been previously described by our group in a smaller population 6 and confirmed in this larger population. The percentage of ST-segment elevation in patients with LVOT VAs in the current study is lesser than in the former one, 60% versus 27%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The much higher incidence of ST-segment elevation in our patients with RVOT VAs has been previously described by our group in a smaller population 6 and confirmed in this larger population. The percentage of ST-segment elevation in patients with LVOT VAs in the current study is lesser than in the former one, 60% versus 27%.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is an increasing amount of evidence suggesting the presence of a substrate within the RVOT in patients with VAs originating from the RVOT. [2][3][4][5][6] In the current study we found the presence of LVAs in 62% of cases using a quadripolar catheter and a point-by-point methodology, whereas Letsas et al 5 mapped the RVOT with multipolar catheters and found a similar result, respectively, the presence of LVAs in 18 out of 28 patients (64%) of cases. The LVAs described by all those authors could not be detected by LGE CMR in none.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…6 However, previous studies have shown the presence of low voltage areas (LVAs) in the RVOT of patients undergoing catheter ablation of frequent idiopathic PVCs. [7][8][9][10][11] As previously, reported by our group, LVAs were predicted by the presence of ST-elevation in V1 or V2 at the level of the second intercostal space (2nd ICS). 9,10 Furthermore, the presence of discrete diastolic potentials (DPs) on the bipolar intracardiac electrograms at the successful ablation site have also been described previously.…”
Section: Discussionsupporting
confidence: 60%
“…[7][8][9][10][11] As previously, reported by our group, LVAs were predicted by the presence of ST-elevation in V1 or V2 at the level of the second intercostal space (2nd ICS). 9,10 Furthermore, the presence of discrete diastolic potentials (DPs) on the bipolar intracardiac electrograms at the successful ablation site have also been described previously. [12][13][14] These are low amplitude potentials, occurring after the T wave of the ECG in sinus rhythm, that become presystolic, preceding the local bipolar ventricular electrogram during the PVCs.…”
Section: Discussionsupporting
confidence: 60%